Secretoneurin gene therapy improves hind limb and cardiac ischaemia in Apo E−/− mice without influencing systemic atherosclerosis. (6th November 2014) - Theurl, Markus; Schgoer, Wilfried; Albrecht-Schgoer, Karin; Lener, Daniela; Wolf, Dominik; Wolf, Maria; Demetz, Egon; Tymoszuk, Piotr; Tancevski, Ivan; Fischer-Colbrie, Reiner; Franz, Wolfgang-Michael; Marschang, Peter; et al.
Abstract: Aims: Hypercholesterolaemia is a major risk factor for cardiovascular diseases and has been shown to influence angiogenesis in the hind limb ischaemia (HLI) model. The impaired up-regulation of angiogenic factors seems to be one of the underlying mechanisms for reduced vessel formation. Since we found that secretoneurin (SN) is up-regulated in hypoxic skeletal muscle cells and exerts beneficial effects in myocardial and HLI, we hypothesized that SN therapy might improve neovascularization in hypercholesterolaemic Apo E −/− (Apo E knockout) mice suffering from an impaired vascular response. Methods and results: For in vitro experiments, endothelial cells (ECs) were incubated with oxidized low-density lipoprotein (oxLDL) to mimic hypercholesterolaemia. EC function was impaired by oxLDL, but SN induced EC proliferation and in vitro tube formation under these conditions. In the HLI model, injection of SN plasmid resulted in a significant better outcome regarding blood flow recovery, amputation rate, and vessel density. In the myocardial infarction (MI) model, the SN group showed improvement in cardiac parameters. Aortic plaque area was not influenced by local SN injection. Interestingly, SN-induced recruitment of angiogenic monocytic cells was abolished under hypercholesterolaemia. Conclusions: SN gene therapy exerts beneficial effects in cardiovascular animal models in Apo E −/− mice without influencing atherosclerosis and might qualify as a promising therapy for cardiovascular disorders.